Effect of high flow hemodialysis on the dose of erythropoietin in patients with chronic renal failure - Aguilar-Rodríguez, Ana (2023)
Objective:  To evaluate the requirements of erythropoietin (EPO) after changing low membrane flow to high in patients on hemodialysis. Secondly, to evaluate changes in serum levels of beta 2 microglobulin, C-reactive protein (CRP) and ferritin. Methods: A retrospective-observational study was carried-out in patients on hemodialysis in two centers in Peru. Clinical and demographic characteristics of patients were reported. Levels of hemoglobin, ferritin saturation percentage, ferritin, Kt/V and EPO baseline doses and each three months for one year after changing the dialyzer were measured. Additionally, serum levels of C-reactive protein and beta 2 microglobulin at 3, 6 and 12 months were obtained. Results: A total of 58 were included; baseline EPO levels were 5 763.55 ± 3 000.69 UI/week and at 12 months were 4 031.18 ± 2663.95 UI/week (p=0.000); baseline hemoglobin was 11.10 ± 1.24 g/dl and 11.69 ± 1.28 g/dl (p=0.077) after 12 months. Serum levels of beta 2 microglobulin dropped from 45.64 ± 11.39 mg/l at baseline to 26.26 ± 8.02 mg/l at one year (p=0.000). Conclusions: EPO doses dropped 30% at 12 months with no changes in hemoglobin. Beta 2 microglobulin dropped 42.5% after one year.